2016
DOI: 10.18805/ijar.8560
|View full text |Cite
|
Sign up to set email alerts
|

Study of mutations in aminolevulinic acid dehydratase (ALAD) gene in cattle from fly ash zone in Maharashtra, India

Abstract: The experiment was undertaken collaboratively at the Department of Animal Genetics and Breeding, Nagpur Veterinary College, Nagpur; National Environmental Engineering Research Institute (NEERI), Nagpur to study the mutagenic effect of fly ash on bovine Amino Levulinic Acid Dehydratase (ALAD) gene. DNA was extracted from blood samples of 49 fly ash exposed cattle born and reared in vicinity of two Thermal Power Plants, Koradi and Khaperkheda and 41 healthy animals reared at organised farms located more than 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Elevated blood lead levels have been linked to increased risk of pregnancy complications, such as gestational hypertension, preeclampsia, and preterm birth. Additionally, lead exposure during pregnancy can negatively impact fetal development, leading to developmental delays, cognitive impairments, and behavioral problems in children (Behera et al2016) [28] . According to Li et al, ALAD plays an important role in the health effects of lead poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated blood lead levels have been linked to increased risk of pregnancy complications, such as gestational hypertension, preeclampsia, and preterm birth. Additionally, lead exposure during pregnancy can negatively impact fetal development, leading to developmental delays, cognitive impairments, and behavioral problems in children (Behera et al2016) [28] . According to Li et al, ALAD plays an important role in the health effects of lead poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the ALAD gene were linked to the phenotypic expression of potentially toxic metal by fly ash exposure in cattle born near thermal power plants, being pointed as a candidate for genomic studies related to metal toxicity 26 . Our results indicated that ALAD is a candidate linked to minerals in general, including potentially toxic metals.…”
Section: Discussionmentioning
confidence: 99%